WISDOM SERVICE PROGRAM TAHFIZ SCHOOL FOR AL-KITAB ORPHANTS, SELANGOR, MALAYSIA - Herman Fithra; Mohd. Heikal; Jullimursyida; Teuku Zulkarnaen; Darmawati; Rico Nur Ilham; Ahmad Fauzul Hakim Hasibuan (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
This service is very important to carry out because it is necessary to carry out an activity for the Al-Kitab Tahfiz Orphans School Tahfiz Program, Selangor. It is also hoped that this activity will collaborate with alumni of the Tahfiz School for AlKitab Orphans (STAY AlKitab) Beranang so that they can continue their studies at Malikussaleh University. Following up on the matters above, it is necessary to visit the Tahfiz School for AlKitab Orphans (STAY AlKitab)